PEMBELAJARAN PENGENALAN KOSAKATA BAHASA INGGRIS MELALUI MEDIA AUDIO VISUAL - Lestari, Kasihani; Yuniarni, Desni; Lukmanulhakim, Lukmanulhakim (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research is motivated by the importance of introduction of English Vocabulary by teachers in early childhood. This research uses qualitative approach and descriptive method. This study aims to obtain information about the learning activities of English vocabulary introduction in early childhood from the preparation stage, implementation to the evaluation stage. This research was conducted at TK Kristen Immanuel I Pontianak Selatan research subjects of A6 group English teachers and Head of Kindergarten. Based on the results of research and data analysis concluded that: 1. Planning learning activities introduction of English Vocabulary through audio visual media is categorized well, because the teacher has done the planning by looking at the needs and abilities of children. 2. Implementation of learning activities to introduce English Vocabulary through audio visual media is categorized well, because in the implementation of teacher learning activities have used the media and how to deliver an interesting so easy to understand the child. 3. Evaluation of learning activities of English Vocabulary introduction through audio visual media is categorized well, because the teacher has done evaluation when the learning activity took place and after the learning activity is completed. Keywords: English Vocabulary, Audiovisual Media